Penerapan Model Beneish (1999) dan Model Altaman (2000) dalam Pendektesian Kecurangan Laporan Keuangan - Rima Novi Kartikasari (Jurnal Akuntansi Multiparadigma, 2010)
Financial fraud is costly and it can be done by almost everyone within (and outside of) an organization. Prevention through early detection of fraud is an important way to reduce fraud. The objective of this research is to prove whether certain models may be utilized to detect financial statement fraud. This study is using Beneish’s (1999) and Altman (2000) models to detect financial statement fraud. Two selected samples that meet with pre-determined criterion have been selected and explored. The result of the study shows that those models can be used to detect financial statement fraud.